2021
DOI: 10.1111/mve.12560
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Rickettsia spp. in chigger mites in Taiwan

Abstract: The genus Rickettsia is the causative agent of several rickettsial diseases that are primarily transmitted by hard ticks. The occurrence of Rickettsia in chigger mites, which are vectors of scrub typhus in the western Pacific region, has been infrequently investigated. We identified Rickettsia spp. in chiggers collected from small mammals in six counties of Taiwan. Moreover, by capitalising on parallel Rickettsia detections on small mammals and their infested ticks and fleas, we were able to identify Rickettsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In this study, we provide the first evidence of Rickettsia infection in chiggers collected from rodents within North America, a significant extension of recent work finding rickettsial DNA in trombiculid mites from South America and Asia [ 10 , 31 , 32 ]. Nucleotide sequence analyses of Rickettsia -specific 23S-5S IGS, 17 kDa, and gltA gene fragments indicated the amplicons from these chiggers were closely related to those in R. felis , R. conorii , R. typhi , and unidentified Rickettsia species.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In this study, we provide the first evidence of Rickettsia infection in chiggers collected from rodents within North America, a significant extension of recent work finding rickettsial DNA in trombiculid mites from South America and Asia [ 10 , 31 , 32 ]. Nucleotide sequence analyses of Rickettsia -specific 23S-5S IGS, 17 kDa, and gltA gene fragments indicated the amplicons from these chiggers were closely related to those in R. felis , R. conorii , R. typhi , and unidentified Rickettsia species.…”
Section: Discussionmentioning
confidence: 63%
“…Nucleotide sequence analyses of Rickettsia -specific 23S-5S IGS, 17 kDa, and gltA gene fragments indicated the amplicons from these chiggers were closely related to those in R. felis , R. conorii , R. typhi , and unidentified Rickettsia species. The most frequently detected rickettsial species in our study, Rickettsia felis , is globally distributed and was found in fleas, mosquitoes, ticks, and chigger mites [ 31 ]. There is increasing evidence that chiggers could be vectors of transitional group rickettsiae, because of their discovery in a variety of field-collected chiggers [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria-positive larvae were obtained from A. agrarius , the Indian mole-rat B. bengalensis Gray, 1835, B. indica , A. roylei , R. rattus , the buff-breasted rat R. tanezumi flavipectus (Milne-Edwards, 1872), R. tanezumi , the Sikkim rat R. andamanensis (Blyth, 1860), R. exulans , R. norvegicus , R. losea , Rattus spp., the small white-toothed rat B. berdmorei (Blyth, 1851), T. belangeri (mentioned as T. belangeri persurae ), T. glis and S. murinus (mentioned as S. murinus fulvo-cinerea) as well as from the moist marshlands (host-questing larvae). The above observations were made in Australia, China, India, Indonesia, Malaysia, Myanmar, Pakistan, Papua New Guinea, Philippines, Singapore, Taiwan (including Pescadores), Thailand and Vietnam [ 10 , 14 , 23 , 40 , 46 , 49 , 51 , 52 , 68 , 78 , 83 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory reared individuals originating from larvae captured in nature were also positive for Mycobacterium sp. Lehmann and Neumann, 1896 (Actinomycetota, Mycobacteriales, Mycobacteriaceae) Infected larvae were obtained from the bodies of A. agrarius , B. indica , R. exulans , R. losea , R. rattus and R. tanezumi captured in Taiwan and Thailand [ 23 , 29 , 84 , 85 , 97 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation